KONSEP ILMU DALAM PANDANGAN ISLAM - Shomiyatun, Shomiyatun (Universitas Ahmad Dahlan, 2017)
The concept of science in term of Islam is ulama?s (Islamic scientists?) thought on understanding, viewing, locating, classifying, dan treating science. It includes what science is obliged to study and to practice and what science is not. It also includes how to view useful science and what its criteria are. The method of research is qualitative library one supported with observation. The objective is to convey the importance of ulama?s concept of science. This is education which should continuously be given and kept going to stimulate, guide and teach students so that they have abilities, skills and complete personalities and science lights and guides them to usefull lives. That is important because science, technology and religion make life much easy. However behind the easyness various big problems come to threaten people when they are careless and wrong in understanding the concept of science and technology. The developed study and classification of science help students learn it easily becase they have limited time. Moslems are obliged to have Islamic concept of science and to study and to practice it. The classification of science without relevant concept is dangerous. The concept of Islamic religious and wordly sciences is not appropriate. The religious science is Alquran and Hadits while worly one is natural science. The concept is dichotomy and shows that natural science is not a part of Islamic science and that Islamic science does not develop as the natural one. The article critizes the classification of natural and Islamic sciences. The classification is wrong. Islam teaches that science is integrated and useful for human being and nature. The wrong concept and classification result fatal errors and should be critized and corrected.